Predictive Factors for Target Organ Injuries in Hypertensive Individuals - Paz Landim, Manoel; Cosenso-Martin, Luciana Neves; Polegati Santos, Aleandra; Roma Uyemura, Jessica Rodrigues; Barufi Fernandes, Leticia; Silva Lopes, Valquiria da; Yugar-Toledo, Juan Carlos; Vilela-Martin, Jose Fernando (Integrated blood pressure control, 2021)
The causal relationship between systemic arterial hypertension and target organ damage (TOD) is well known, as well as the association with cardiovascular risk factors (CV). Ambulatory blood pressure monitoring (ABPM) is important in monitoring hypertension and assessing the risk of TOD. To evaluate the relationship between blood pressure (BP) and clinical and biochemical parameters in the development of TOD in hypertensive patients. This was a retrospective cohort study with 162 hypertensive patients followed for an average period of 13 years. The TOD investigated were left ventricular hypertrophy (LVH), microalbuminuria, coronary artery disease (CAD) and stroke. Blood pressure was assessed by ABPM and LVH using echocardiogram and electrocardiogram, respectively. Biochemical-metabolic tests and 24-hour microalbuminuria were performed at baseline and follow-up. The P-value <0.05 was considered significant. The average age was 69±11.8 years, with a predominance of women (64.8%), white ethnicity (79.6%) and diabetics (78.4%). ABPM showed a significant reduction in BP values during follow-up, although without association with TOD (microalbuminuria, stroke, and CAD), except for LVH that showed a correlation with sleep BP ≥120/70 mmHg (P=0.044). The most frequent TODs were LVH (29.6%), microalbuminuria (26.5%), CAD (19.8%) and stroke (17.3%). In the follow-up, there was an association between LVH and diabetes; microalbuminuria was associated with diabetes and triglycerides; stroke was associated with HDL-cholesterol (HDL-c), microalbuminuria and carotid disease. CAD showed a relationship with age and HDL-c. Predictive factors for TOD are age, microalbuminuria, diabetes, HDL-c, triglycerides and carotid disease. Nocturnal BP is correlated with LVH. The absence of a relationship between ABPM and other TODs can be explained by the use of effective drugs, improvement of metabolic and blood pressure parameters.